2020
DOI: 10.1055/s-0040-1716552
|View full text |Cite
|
Sign up to set email alerts
|

Microfracture versus Enhanced Microfracture Techniques in Knee Cartilage Restoration: A Systematic Review and Meta-Analysis

Abstract: This study aimed to compare the efficacy and safety of the microfracture (MFx) and microfracture augmented (MFx + ) techniques for the treatment of cartilage defects of the knee. The PubMed and EMBASE databases were searched from 1 January, 1950 to 1 May, 2019. RevMan5.3 was used to perform statistical analysis. Relative risk was calculated for binary variables, and weighted mean difference and standardized mean difference (SMD) were measured for continuous variables. The 95% confidence interval (CI) of each v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These findings are consistent with 2 previous systematic reviews that similarly reported improvement in Lysholm scores when MFx treatment was augmentation. 1,55…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with 2 previous systematic reviews that similarly reported improvement in Lysholm scores when MFx treatment was augmentation. 1,55…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when comparing MFx + augmentation to MFx alone, the authors noted in a subjective synthesis that 2 randomized controlled trials (RCTs) demonstrated significantly greater improvements in IKDC and KOOS scores after MFx + augmentation, with 2 other RCTs demonstrating comparable postoperative outcomes. Similarly, a systematic review and meta–analysis by Wen et al 55 evaluating 13 clinical trials, comprising a total of 635 patients, compared the efficacy and safety of isolated MFx versus MFx + augmentation. Comparable with the findings from our investigation, the authors reported no significant difference in IKDC, WOMAC, and VAS pain scores between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior results of the combination of HTO and cartilage regeneration procedures compared with HTO alone have been reported in several studies [ 21 , 22 ]. Despite promising results regarding cartilage regeneration procedures using MSC-based orthobiologics, the optimal cartilage regeneration procedure that can be performed with HTO remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For symptomatic defects smaller than 2 cm 2 , microfractures (MFx) have been proposed 9 12 . MFx is a bone marrow stimulating procedure of simple execution which can be conducted in a fully arthroscopic fashion 13 . During MFx, the cartilage is debrided to its viable border, and microfractures are performed to promote cell migration from the subchondral bone 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%